Psychological distress, anger and quality of life in polycystic ovary syndrome: associations with biochemical, phenotypical andsocio-demographic factors - Lidia Borghi; Daniela Leone; Elena Vegni; Valentina Galiano; Corina Lepadatu; Patrizia Sulpizio; Emanuele Garzia (Journal of Psychosomatic Obstetrics and Gynecology, 2018)
Objective: To investigate the association between polycystic ovary syndrome (PCOS) and psychological disturbances, including anger. To analyze whether the biochemical/phenotypical features of PCOS play a role in the type and severity of psychological disorders. Material and methods: This case–control study included 30 PCOS patients meeting NIH criteria and 30 non-PCOS women referring to Reproductive Medicine Unit for infertility. Complete clinical and biochemical screening and the self-reported psychological data [Symptom Check List 90-R (SCL-90-R); Short-Form Health Survey 36 (SF-36); and State-Trait Anger Expression Inventory-2 (STAXI-2)] were collected. Statistical analyses were performed with SPSS-21. Results: Compared with control women, women with PCOS reported significantly higher scores on SCL-90-R scales of somatization, anxiety, hostility, psychoticism, overall psychological distress and a number of symptoms. At STAXI-2, patients with PCOS scored higher in trait-anger and in the outward expression of anger, while lower in outward anger-control; PCOS patients had significantly lower scores on SF-36 scales of physical functioning and bodily pain. Hirsutism was directly associated with anxiety. Regarding the associations between phenotypical/biochemical features and psychological distress in PCOS patients, results showed that waist-to-hip ratio is inversely related to anxiety, psychoticism, hostility and to the indexes of psychological distress; such inverse relationship was also seen between plasmatic levels of testosterone and trait-anger, and between total cholesterol and hostility. Conclusions: Results were consistent with the previous literature on the well-being of PCOS women (in particular for anxiety and quality of life [QoL]) but failed to find evidence for depression. The relationship between psychological distress and the features of the syndrome highlighted the role of hirsutism. With respect to hyperandrogenemia, our data rejected its involvement in the elevated negative mood states and affects. Adopting an interdisciplinary approach in the PCOS patients’ care, anger showed to be common and deserves major consideration.